Analysis of Work Environment, Attitude, Coaching, and Servant Leadership on Job Satisfaction Mediated by Career Development (Literature Review Study) - Wenny Desty Febrian; Indra Sani (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to analyze the factors that cause the achievement of good management performance, this study uses a literature review from google scholar, ScienceDirect, and Emerald to review relevant previous articles, and supporting factors that are suspected as factors that can achieve management performance include Work Environment, Attitude, Coaching, and Servant Leadership, Career Development, the findings of this study are several variables that do not affect the dependent variable. The gaps found in previous research are the basis for this research and this research can answer these gaps in the conclusion.